Gastrocnemius Muscle Structural and Functional Changes Associated with Domestication in the Turkey - Kristin K. Stover; David A. Sleboda; Elizabeth L. Brainerd; Thomas J. Roberts (Animals, 2021)
Selection for increased muscle mass in domestic turkeys has resulted in muscles twice the size of those found in wild turkeys. This study characterizes muscle structural changes as well as functional differences in muscle performance associated with selection for increased muscle mass. We compared peak isometric force production, whole muscle and individual fiber cross-sectional area (CSA), connective tissue collagen concentration and structure of the lateral gastrocnemius (LG) muscle in wild and adult domestic turkeys. We also explored changes with age between juvenile and adult domestic turkeys. We found that the domestic turkey’s LG muscle can produce the same force per cross-sectional area as a wild turkey; however, due to scaling, domestic adults produce less force per unit body mass. Domestic turkey muscle fibers were slightly smaller in CSA (3802 ± 2223 μm2) than those of the wild turkey (4014 ± 1831 μm2, p = 0.013), indicating that the absolutely larger domestic turkey muscles are a result of an increased number of smaller fibers. Collagen concentration in domestic turkey muscle (4.19 ± 1.58 μg hydroxyproline/mg muscle) was significantly lower than in the wild turkeys (6.23 ± 0.63 μg/mg, p = 0.0275), with visible differences in endomysium texture, observed via scanning electron microscopy. Selection for increased muscle mass has altered the structure of the LG muscle; however, scaling likely contributes more to hind limb functional differences observed in the domestic turkey.